Efek Hepatoprotektif Ekstrak Etanol Brokoli (Brassica oleracea L. var. italica) terhadap Kadar Malondialdehid Hepar Tikus Wistar yang Diinduksi DMBA (Hepatoprotective Effect of Ethanolic Extract of Broccoli (Brassica oleracea L. var. italica) on Liver Ma - Dear Farah Sielma; Elly Nurus Sakinah; Yudha Nurdian (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
DMBA (7,12-Dimethylbenz(α)antracene) is a prototype of Polycyclic Aromatic Hydrocarbons (PAHs) which is present in automobile exhaust, cigarette smoke, and wood stoves. DMBA is converted into its reactive metabolites DMBA-DE and cause liver cell membrane lipid peroxidation, which results in an increased of liver malondialdehyde (MDA) levels. Broccoli contains flavonoid that able to prevent lipid peroxidation. The current study was conducted to find out the different hepatoprotective effect of ethanolic extract of broccoli against DMBA-induced hepatotoxicity in wistar rats using liver MDA as a marker. A total of 24 male wistar rats were divided into six groups, consisting of normal control (distilled water), negative control (DMBA), and treatment (ethanolic extract of broccoli in doses of 250, 500, 1000, and 2000 mg/kgBW). Rats were treated for 7 days prior to a single dose of DMBA on the 8th day of treatment. Liver tissue samples were taken on the 12th day for measurement of liver MDA levels. Data were analyzed using One Way ANOVA followed by Post Hoc Test LSD. The present study showed significant differences on liver MDA levels between groups (p<0.001). This study concluded that there were different hepatoprotective effects of ethanolic extract of broccoli treatment on liver MDA levels in wistar rats induced by DMBA. Keywords: ethanolic extract of broccoli, DMBA, malondialdehyde, hepatoprotective